FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINDAKAN PEMBERIAN MAKANAN PENDAMPING ASI (IMP-ASI) DI DESA DAMULI PEKAN KECAMATAN KUALUH SELATAN KABUPATEN LABUHANBATU UTARA TAHUN 2024 - Silaen, Meliyanti (TOUR HEALTH JOURNAL, 2024)
Background: Complementary Feeding for Breastfed Infants (MP-ASI) refers to food or beverages given as a transition after breastfeeding. Only 49.8% of mothers provide exclucive breastfeeding for 6 months, due to the high rate of early introduction of complementary feeding. The lack of exclusive breastfeeding for infants can affect the quality of life of future generations and impact the national economy (Fadhila & Ninditya, 2016). Purpose: This study aims to analyze the factors associated with the practice of providing complementary feeding (MP-ASI). Method: This research uses an analytical study design with a cross-sectional approach, conducted in Damuli Pekan Village, Kualuh Selatan District, North Labuhanbatu Regency in 2024. The population includes mothers with children aged 0-6 months, totaling 84 hauseholds, and a sample size of 46 mothers. The sample was obtained using the accidental sampling technique. Data collection was carried aout through interviews using a questionnaire that had been tasted for validity and reliability. Data analysis was performed using the Chi-Square statistical test. Results: The results of the study indicate that there is a relationship between age, income, education, and knowladge with the provision of MP-ASI in Damuli Pekan Village, Kualuh Selatan District, North Labuhanbatu Regency. Disscusion and Conclusion: It is recommended that healthcare workes, especially at Simangalam Health Center, Kualuh Selatan, enhance their role in educating the community about the proper methods of providing MP-ASI to increase mothers knowledge on appropriate complementary feeding practices.